Developing an Ethno-Ecotourism Environmental Education Model for Sustainable Coastal Tourism in Aceh Indonesia - Dian Aswita; Nafisah Hanim; Cut Ratna Dewi; Nur Aisyah Ainun; Firdaus Daud; Syamsul Rizal (Jurnal Ilmiah Peuradeun, 2026)
Tourism expansion in environmentally sensitive coastal areas continues to intensify ecological pressures, while conventional environmental education often remains disconnected from indigenous socio-cultural realities. Although customary institutions have long contributed to environmental stewardship, limited research has transformed indigenous governance into a structured educational framework for sustainable tourism. This study aimed to develop and validate an Ethno-ecotourism-based Environmental Education Model that operationalizes Acehnese customary institutions as pedagogical mechanisms for sustainability education. Using a Research and Development (R&D) approach through the Four-D framework and a sequential explanatory mixed-method design, data were collected through interviews and observations involving 15 key informants, expert validation by seven specialists, and practicality testing with 30 tourism practitioners. Qualitative data were analyzed using the interactive model of Huberman and Saldaña, while quantitative data were examined using descriptive statistics. The findings indicated that the model was both valid and practical, with the social system emerging as its strongest component. The study demonstrated that indigenous governance could serve as an educational infrastructure that strengthened environmental responsibility, community-based conservation, and sustainable tourism. By integrating customary law into a validated pedagogical framework, this research contributes to the theory of environmental education and provides a culturally responsive pathway to sustainability in indigenous and coastal communities.